Realization Of Temperature Measurement Using Semiconductor Based Photonic Crystal Structure (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Semiconductor based two-dimensional triangular photonic crystal structures (TPCS) are focused in the present research to measure the temperature where the semiconductors like Silicon, Germanium, Indium Arsenide, and Indium Antimonide are used as the background materials. The triangular strctures are exposed to a light source of wavelength 10.59μm to estimate the  temperatures. Since the abosorbtance of the background materials is zero at incident signal,the energy of transmitted light solely depends on the reflected light energy. Further plane wave expansion (PWE) technique has been implemented in analysing the nature of the photonic bandgap (PBG) of the photonic structure which is a decisive factor for the calculation of output energy. The results are obtained by appraising the energy level of transmitted light through the photonic crystal structure.